S2: Fatty acid data supplement from Ambient temperature and algal prey type affect essential fatty acid incorporation and trophic upgrading in an herbivorous marine copepod - Laura Helenius; Suzanne Budge; Heather Nadeau; Catherine L. Johnson (2020)
Major fatty acids in algal prey and copepods in feeding experiments at different temperature treatments